Group 8 Metallomacrocycles – Synthesis, Characterization, and Stability. Issue 34 (13th November 2015) - Ludlow, James M.; Guo, Zaihong; Schultz, Anthony; Sarkar, Rajarshi; Moorefield, Charles N.; Wesdemiotis, Chrys; Newkome, George R.
Abstract: The one‐step synthesis of the first homoleptic metallomacrocycle is reported. Characterization of the Os II complex, along with its Fe II and Ru II analogues, was accomplished by NMR spectroscopy, ESI‐MS, TWIM‐MS, gradient tandem‐MS, CV, luminescence and UV/Vis spectroscopy. Center‐of‐mass collision energies, derived from gradient tandem‐MS, reveal that the ‐based structures are more stable than those of . Abstract : Synthesis and characterization of group 8 metallocycles is reported. Center‐of‐mass collision energies determined by gradient tandem‐MS (g‐MS 2 ) indicate relative stability in the order of Ru II > Os II > Fe II . The metallocycles were also characterized by NMR spectroscopy, CV, ESI‐TWIM‐MS, UV/Vis spectroscopy, and photoluminescence studies.